Synthesis and physico-chemical properties of high-quality expanded graphite - Yu. V. Hrebelna; E. M. Demianenko; M. I. Terets; V. V. Lobanov; S. V. Zhuravskyi; O. M. Ignatenko; K. O. Ivanenko; Yu. I. Gornikov; M. T. Kartel; Yu. I. Sementsov (Хімія, фізика та технологія поверхні)
The purpose of the work is to establish the possibility of obtaining expanded graphite of high purity (carbon content more than 99.5 % wt.) from flotation-enriched graphite (carbon content 94–97 % wt.) by combining into one process intercalation of graphite with a solution of potassium dichromate in concentrated sulfuric acid with subsequent hydrolysis, and chemical purification using solutions of ammonium bifluoride in sulfuric or hydrochloric acid and Trilon B in an alkaline buffer as purification reagents, and to confirm this possibility by quantum chemical calculations. It has been experimentally shown that combining oxidized graphite synthesis and its chemical purification into one process allows obtaining expanded graphite of high purity, with a carbon content of 99.75–99.85 % wt. The methods of X-ray diffraction and thermogravimetry show that the interaction of oxidized graphite (the residual compound of intercalation of graphite with sulfuric acid) with cleaning reagents does not reduce the ability to expand. The magnitude of the mass loss of oxidized graphite according to various variants of chemical post-cleaning and the temperature range of such loss remain practically unchanged.